2023
DOI: 10.3390/ijms24065626
|View full text |Cite
|
Sign up to set email alerts
|

Revising the Landscape of Cytokine-Induced Killer Cell Therapy in Lung Cancer: Focus on Immune Checkpoint Inhibitors

Abstract: Undeniably, immunotherapy has markedly improved the survival rate of cancer patients. The scenario is no different in lung cancer, where multiple treatment options are now available and the inclusion of immunotherapy yields better clinical benefits than previously used chemotherapeutic strategies. Of interest, cytokine-induced killer (CIK) cell immunotherapy has also taken a central role in clinical trials for the treatment of lung cancer. Herein, we describe the relative success of CIK cell therapy (alone and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 74 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…For instance, CIK cellular immunotherapy provides a pivotal role in clinical trials for the treatment of cancer. 296 The CIK cell therapy combination with DCs has been relatively successful in lung cancer clinical trials. 297 , 298 Combination therapy with CIK cells and PD1 blocking antibodies showed potential for profound durable responses in NSCLC.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, CIK cellular immunotherapy provides a pivotal role in clinical trials for the treatment of cancer. 296 The CIK cell therapy combination with DCs has been relatively successful in lung cancer clinical trials. 297 , 298 Combination therapy with CIK cells and PD1 blocking antibodies showed potential for profound durable responses in NSCLC.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…And these immunotherapeutic treatments have achieved a certain degree of effectiveness. For instance, CIK cellular immunotherapy provides a pivotal role in clinical trials for the treatment of cancer 296 . The CIK cell therapy combination with DCs has been relatively successful in lung cancer clinical trials 297,298 .…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…After two courses of sintilimab treatment, SD was achieved; however, the symptoms, including cancer-associated pain, fatigue, malaise, a loss of appetite and poor mental state were not significantly improved. CIK cells have been suggested to improve the quality of life and enhance the effect of anti-PD-1 immunotherapy ( 28 ). Therefore, CIK cell infusions (1–2×10 9 cells/day for 3 consecutive days in each session, once per month and ≥3 days away from the treatment of PD-1 blockade) were added in combination with sintilimab to the subsequent courses of treatment.…”
Section: Case Reportmentioning
confidence: 99%
“…A prospective study of 63 patients with advanced GC showed that the combination of dendritic cell-CIK with S-1 plus cisplatin resulted in promising PFS and OS (70). Furthermore, the adverse effects and toxicity of CIK cell treatment are moderate and easy to control (69,71). NK cells are activated as anti-tumor agents via the loss or downregulation of major histocompatibility complex I molecules, through which tumor cells can escape CTL recognition (72).…”
Section: Adoptive Cell Therapymentioning
confidence: 99%